2017
DOI: 10.1212/wnl.0000000000004598
|View full text |Cite|
|
Sign up to set email alerts
|

Thrombolysis in acute ischemic stroke in patients with dementia

Abstract: Objective:To compare access to intravenous thrombolysis (IVT) for acute ischemic stroke (AIS) and its outcomes in patients with and without dementia.Methods:This was a longitudinal cohort study of the Swedish dementia and stroke registries. Patients with preexisting dementia who had AIS from 2010 to 2014 (n = 1,356) were compared with matched patients without dementia (n = 6,755). We examined access to thrombolysis and its outcomes at 3 months (death, residency, and modified Rankin Scale [mRS] score). Odds rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 22 publications
2
36
0
Order By: Relevance
“…We found that acute reperfusion treatment was less utilized in patients with ischemic stroke who had a history of psychosis. A lower likelihood of reperfusion treatment was also found in patients with pre-stroke dementia in a recent analysis of thrombolysis in Swedish patients (21). However, this difference disappeared when adjusting for pre-stroke functional status.…”
Section: Discussionmentioning
confidence: 69%
“…We found that acute reperfusion treatment was less utilized in patients with ischemic stroke who had a history of psychosis. A lower likelihood of reperfusion treatment was also found in patients with pre-stroke dementia in a recent analysis of thrombolysis in Swedish patients (21). However, this difference disappeared when adjusting for pre-stroke functional status.…”
Section: Discussionmentioning
confidence: 69%
“…While there are few data on thrombectomy in these patients, observational studies of thrombolysis in patients with dementia suggest that mortality and hemorrhage risks are comparable to those without dementia, though functional outcomes may be worse. [22][23][24] In this regard, it is noteworthy that most respondents chose alteplase in the scenario with MCI.…”
Section: Discussionmentioning
confidence: 98%
“…A greater understanding of the differences and similarities between males and females with respect to previous cardiovascular risk factors [1, 17, 18, 20], previous physical or mental condition [21, 22], response to acute stroke therapies, and recovery will hopefully lead to better outcomes in the future.…”
Section: Discussionmentioning
confidence: 99%